CLINICAL AND CYTOLOGICAL DIAGNOSIS OF CHRONIC THYROIDITIS (International Conference on Modern Science and Scientific Studies, 2025)
Autoimmune thyroiditis (AIT) is one of the most common diseases of the thyroid gland (thyroid), with more than 80 years having passed since its description by the Japanese surgeon Hashimoto [6,7,8].